PENGEMBANGAN MODUL REDOKS DAN SEL ELEKTROKIMIA BERBASIS PROBLEM SOLVING DI KELAS XII SMA/MA SEDERAJAT - Ramadhan, Ahmad Khairu; Erviyenni, Erviyenni; Haryati, Sri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Absrtract: This study aims to develop Redox and Elektrochemical Cells module based on problem solving in class XII SMA / MA which is valid based on content, presentation, linguistic, and graphic aspects. This type of research is a research and development (R & D with a 4-D development model that includes Definition, Design, Development, and Dissemination. This research have done to development stage only. The object of this research is a problem-solving module. Data analysis technique is calculation of validation percentage and response questionnaire. The data instrument is validation sheets given to three validators and response questionnaire given to teachers and student. The average score of the variable number of the validity of the module by the validator team, namely the content, presentation, language, and graphics 93.45%, 88.54%, 90o% and 90%, respectively, with the overall average validation module validator team is 90.55% valid. The use of data analysis can be concluded that the Redox and Problem Solving-based electrochemical module can be developed and declared valid to be used for learning in SMA / MA equivalent.Key Words: Module, Problem Solving, Redox and Electrochemical Cell